Answer:
x = 4, y = - 2
Explanation:
Given the 2 equations
3x + 2y = 8 → (1)
2x + 5y = - 2 → (2)
Multiplying (1) by 2 and (2) by - 3 and adding eliminates the x- term
6x + 4y = 16 → (3)
- 6x - 15y = 6 → (4)
Add (3) and (4) term by term to eliminate x , that is
- 11y = 22 ( divide both sides by - 11 )
y = - 2
Substitute y = - 2 into either of the 2 equations and solve for x
Substituting into (1)
3x + 2(- 2) = 8
3x - 4 = 8 ( add 4 to both sides )
3x = 12 ( divide both sides by 3 )
x = 4
solution is x = 4, y = - 2